"I go I die, I stay I die, better to stay and die in my house": understanding the barriers to accessing health care in Timor-Leste. Issue 1 (December 2016) - Price, Jennifer; Soares, Ana; Asante, Augustine; Martins, Joao; Williams, Kate; Wiseman, Virginia
Abstract Background Despite public health care being free at the point of delivery in Timor-Leste, wealthier patients access hospital care at nearly twice the rate of poorer patients. This study seeks to understand the barriers driving inequitable utilisation of hospital services in Timor-Leste from the perspective of community members and health care managers. Methods This multisite qualitative study in Timor-Leste conducted gender segregated focus groups (n = 8) in eight districts, with 59 adults in urban and rural settings, and in-depth interviews (n = 8) with the Director of community health centres. Communication was in the local language, Tetum, using a pre-tested interview schedule. Approval was obtained from community and national stakeholders, with written consent from participants. Results Lack of patient transport is the critical cross-cutting issue preventing access to hospital care. Without it, many communities resort to carrying patients by porters or on horseback, walking or paying for (unaffordable) private arrangements to reach hospital, or opt for home-based care. Other significant out-of-pocket expenses for hospital visits were blood supplies from private suppliers; accommodation and food for the patient and family members; and repatriation of the deceased. Entrenched nepotism and hospital staff denigrating patients' hygiene and personal circumstances were also widely reported. Consequently, some respondents asserted they would never return to hospital, others delayed seeking treatment or interrupted their treatment to return home. Most considered traditional medicine provided an affordable, accessible and acceptable substitute to hospital care. Obtaining a referral for higher level care was not a significant barrier to gaining access to hospital care. Conclusions Onerous physical, financial and socio-cultural barriers are preventing or discouraging people from accessing hospital care in Timor-Leste. Improving access to quality primary health care at the frontline is a key strategy for ensuring universal access to health care, pursued alongside initiatives to overcome the multi-faceted barriers to hospital care experienced by the vulnerable. Improving the availability and functioning of patient transport services, provision of travel subsidies to patients and their families and training hospital staff in standards of professional care are some options available to government and donors seeking faster progress towards universal health coverage in Timor-Leste.